Integrity in Finnish Public Administration-Theoretical aspects and perceptions of citizens based on Citizen Survey 2008 - Mäntysalo, Venla (My University, 2009)
Integrity in public administration is a central theme in the study of administrative ethics. The approach to integrity in this study is a combination of various aspects of administrative integrity. Integrity can be defined in a narrow sense, regarding it as a value and a character of public officials. The concept of integrity in itself is wide, in this study, integrity is seen as a combination of characteristics and values in public administration. Integrity is defined as honesty and truthfulness, impartiality, incorruptness and law-abiding. Integrity in administration contributes to trust in government. Central element of integrity is the absence of corruption. Therefore, integrity violations are analysed, as their level of occurrence relates to administrative integrity. The main theoretical focus is to develop an understanding of the concept of integrity in administration. Due to the ambiguous use of the concept, an outline for measuring integrity is established, via literature review and previous studies. Various integrity violations are taken a closer looked, since their existence defines the integrity of public administration. Core elements such as honesty, impartiality and truthful-ness are connected to integrity. The main goal of the study is to discover how do Finnish citizens esti-mate the integrity of public administration, is it a system comprising of integrity, what areas of integrity are strong, where do possible weaknesses lie, and whether integrity violations deteriorate the adminis-trative integrity in Finland. The empirical study is based on the Citizen Survey 2008, carried out in the University of Vaasa, under the research project Citizens first? Ethical governance in terms of citizens. The citizens answered on questions concerning the ethics of public administration. The response rate of the survey rose to 40%, providing a large data for the study of administrative ethics. Integrity of administration is largely dependent on the integrity of public officials, naturally influenced by the integrity of public organizations and the measures to prevent integrity violations. Honesty, im-partiality, truthfulness, ability to keep commitments, law-abiding and incorruptness are at the core of integrity. Integrity violations undermine these positive aspects of integrity in various ways. Opposites of integrity, such as private gain and greed, increase the likeness of integrity violations. The Finnish citizens estimated the public officials to be rather honest and trustworthy. Impartiality is not as highly appreciated, and on the other side, the ability to keep promises undermines the first as-sumption of trustworthiness, and the ability to keep commitments. A positive evaluation of the integrity in Finnish public administration is citizens’ perception of low level of severe forms of corruption. How-ever, the morality aspect of integrity does not come true, since greed and self-interest seem to be main motivators for public officials. Most severely the citizens estimated that old-boy networks and nepotism distort the integrity of public officials.
Keywords: integrity; public administration; honesty; trust; integrity violations; fi=Hallintotiede : European Civil Servants - kansainvälisen hallinnon ohjelma|